Estimates on Age, Growth, Sex Composition, and Mortality of Silurus lanzhouensis (Chen, 1977) in the Upper Yellow River, China - Peilun Li; Jiacheng Liu; Shuhan Xiong; Tai Wang; Yongjie Wang; Jilong Wang (Fishes)
Silurus lanzhouensis is a large-sized commercial fish species endemic to the mid-upper reaches of the Yellow River, serving as a “Card of Aquatic Biological Species in the Yellow River”. However, due to factors such as overfishing and habitat changes, it has been listed as an endangered species. In order to protect and restore its wild resources, we conducted a detailed study for the first time from 2022 to 2024 on the age composition, growth characteristics, mortality rate, and current status of resource exploitation of the S. lanzhouensis population in the upper Yellow River. A total of 489 individuals underwent measurements for their total length (L) and body weight (W), with age determination conducted using lapillus otoliths. The collected samples exhibited a spectrum of total lengths spanning from 2.5 to 63.7 cm, body weights ranging from 0.11 to 1974.15 g, and ages ranging from 1 to 6 years. Further analysis of the length–weight relationships unveiled an allometric growth index (b) of 2.9562 for the overall samples, indicating an isometric growth pattern. Additionally, insights into the growth characteristics of S. lanzhouensis were provided by the von Bertalanffy growth function, revealing an asymptotic total length (L∞) of 119.30 cm and a growth coefficient (K) of 0.1278 yr−1. The growth characteristic index (φ) totaled 3.2598, suggesting a moderate growth rate in comparison to other Silurus species. The total mortality rate (Z) recorded for the population of S. lanzhouensis was found to be 0.5296 yr−1. Through the application of three distinct methodologies on exhaustive samples, the average natural mortality rate (M) was calculated to be 0.3105 yr−1. Consequently, the fishing mortality rate (F) for the entire sample set was determined to be 0.2191 yr−1, leading to an exploitation rate (E) of 0.4137. Based on the survey findings, it is evident that the population of S. lanzhouensis has not been subjected to over-exploitation, attributable to ongoing stock enhancement. These results also provide foundational data for the protection and restoration of S. lanzhouensis in the upper Yellow River.